G578(P) Polycystic ovarian syndrome in adolescents: towards the discovery of novel non-invasive biomarkers. (May 2019) - Gunn, HM; Forsyth, VS; Skinner, R; Milne, B; Mills, K; Steinbeck, K
Abstract : Background: Polycystic ovarian syndrome (PCOS) is the most common hormone disorder in adolescent and young adult females, affecting 4%–20% of the population. PCOS is associated with metabolic dysfunction, pro-inflammation and mood disorders. Despite this, it is poorly understood in younger adolescents, and diagnosis and management remain challenging. Aims: To better understand the clinical phenotype of PCOS in adolescents. To undertake discovery proteomic urine profiling to identify novel non–invasive biomarkers of PCOS. Method: In this prospective longitudinal study, females aged 12–19 years meeting NIH diagnostic criteria for PCOS were recruited from adolescent endocrine and gynaecology clinics. The following were measured at baseline and annual follow-up: pituitary, adrenal and ovarian hormones, anti-müllerian hormone, inflammatory and metabolic markers including an oral glucose tolerance test. Psychometric questionnaires, menstrual records, pubertal assessment, anthropometric parameters and trans-abdominal pelvic ultrasounds were also undertaken. Urine samples were obtained for mass spectrometry discovery proteomic profiling. Results: To date, 37 participants have been recruited (median age 15.0 years, range 12.6–18.3), and 22 have completed annual follow-up. Clinical signs at presentation included acne (89%), hirsutism (78%), acanthosis nigricans (49%) and overweight/obesity (81%). Two-thirds of participants had depressive or anxiety symptoms. Only one-third were known to mental health services. Metabolic dysfunction was common; elevated body fat (88%), dysplidaemia (24%), insulin resistance (62%), and impaired fasting glucose, impaired glucose tolerance or type 2 diabetes (40%). AMH was elevated in one-third of participants and three-quarters had an elevated free androgen index. Elevated inflammatory markers (CRP/ESR) were present in 40% participants. Only three participants had definitive ultrasonographic evidence of PCOS. Interventions included lifestyle advice only (27%), combined oral contraceptive pill (COCP) ±anti androgen (16%), metformin (30%) or metformin +COCP ± anti-androgen (27%). Conclusion and future directions : Diagnosing PCOS in adolescents remains challenging; acne and irregular menstrual cycles are common and ultrasonographic diagnosis of PCOS is suboptimal. Given the high prevalence of metabolic and mental health disorders, early diagnosis and intervention are imperative. We are currently undertaking discovery urine proteomic analysis to identify novel non-invasive biomarkers of PCOS. Subsequently, we will create a clinically translatable assay to aid diagnosis and management of this common adolescent condition.